Psychological Status and Influencing Factors of Hospital Medical Staff During the COVID-19 Outbreak - Yao, Yang; Tian, Yao; Zhou, Jing; Diao, Xin; Cao, Bogan; Pan, Shuang; Di, Ligai; Liu, Yan; Chen, Hui; Xie, Chunxia; Yang, Yuanli; Li, Feiyu; et al. (Frontiers in Psychology, 2020)
Background The aim of this study was to analyze the psychological status of and its influencing factors in health care workers (HCWs) during the coronavirus disease 2019 (COVID-19) outbreak so as to provide sufficient theory and scientific basis for the formulation and implementation of relevant policies and measures in improving the psychological status of HCWs. Method During February 1 to February 20, 2020, 1,002 members of the HCWs from Xi’an and Wuhan completed a 12-item questionnaire regarding pressure about the COVID-19 influenza pandemic, along with the 12-item General Health Questionnaire (GHQ-12). The GHQ-12 scale was divided by three points. The positive group was scored more than 3. All data were analyzed by SPSS. Results More than half of the participants (61.1%) reported psychological distress. The HCWs have sufficient information about the COVID-19 symptoms, prognosis, treatment, infection route, and preventive measures (medians ranged from 6/9 to 8/9). Female, engaged in clinic work less than 7 years, married person, and working in Wuhan were risk factors affecting the psychological status of HCWs (P < 0.05). Conclusion Psychological distress is common in HCWs during the COVID-19 outbreak. Hospitals and relevant departments should provide psychological support to HCWs, and strict infection control measures should be developed.